Объяснение:
(х+3)²=16
+6x+9=16
по виете:
x1+x2=-6
x1*x2=9
x1=-3
x2=-3
по дискриминанту:
a=1 b=6 c=9
D=-4ac
D=36-4*1*9
D=0=0 ==> один корень
x=
x=-3
ответ -3
(1-2x)(1+2x)=x
1-4=x
-4-x+1=0 ║*(-1)
4+x-1=0
a=4 b=1 c=-1
D=1+4*4*1
D=17
x1,2=
x1=
x2=
Отв: ;
Объяснение:
(х+3)²=16
по виете:
x1+x2=-6
x1*x2=9
x1=-3
x2=-3
по дискриминанту:
a=1 b=6 c=9
D=
-4ac
D=36-4*1*9
D=0=0 ==> один корень
x=![\frac{-b}{2a}](/tpl/images/1115/4523/1510a.png)
x=![\frac{-6}{2}](/tpl/images/1115/4523/c21b5.png)
x=-3
ответ -3
(1-2x)(1+2x)=x
1-4
=x
-4
-x+1=0 ║*(-1)
4
+x-1=0
a=4 b=1 c=-1
D=1+4*4*1
D=17
x1,2=![\frac{-1+-\sqrt{17} }{8}](/tpl/images/1115/4523/3ba3d.png)
x1=![\frac{-1+\sqrt{17} }{8}](/tpl/images/1115/4523/db856.png)
x2=![\frac{-1-\sqrt{17} }{8}](/tpl/images/1115/4523/7400c.png)
Отв:
; ![\frac{-1-\sqrt{17} }{8}](/tpl/images/1115/4523/7400c.png)